Interventions to enhance testing, linkage to care, and treatment initiation for hepatitis C virus infection: a systematic review and meta-analysis. (May 2022) - Cunningham, Evan B; Wheeler, Alice; Hajarizadeh, Behzad; French, Clare E; Roche, Rachel; Marshall, Alison D; Fontaine, Guillaume; Conway, Anna; Valencia, Braulio M; Bajis, Sahar; Presseau, Justin; Ward, John W; et al.
Summary: Background: Despite the goal set by WHO to eliminate hepatitis C virus (HCV) as a public health threat, uptake of HCV testing and treatment remains low. To achieve this target, evidence-based interventions are needed to address the barriers to care for people with, or at risk of, HCV infection. We aimed to assess the efficacy of interventions to improve HCV antibody testing, HCV RNA testing, linkage to HCV care, and treatment initiation. Methods: In this systematic review and meta-analysis, we searched MEDLINE (PubMed), Scopus, Web of Science, the Cochrane Central Register of Controlled Trials, and PsycINFO without language restrictions for reports published between database inception and July 21, 2020, assessing the following primary outcomes: HCV antibody testing; HCV RNA testing; linkage to HCV care; and direct-acting antiviral treatment initiation. We also searched key conference abstracts. We included randomised and non-randomised studies assessing non-pharmaceutical interventions that included a comparator or control group. Studies were excluded if they enrolled only paediatric populations (aged <18 years) or if they conducted the intervention in a different health-care setting to that of the control or comparator. Authors were contacted to clarify study details and to obtain additional population-level data. Data were extracted from the records identified into a pre-piloted and standardised data extraction form and a random-effects meta-analysis was used to pool the effects of the interventions on study outcomes. This study is registered in PROSPERO, CRD42020178035. Findings: Of 15 342 unique records identified, 142 were included, which reported on 148 unique studies (47 randomised controlled trials and 101 non-randomised studies). Medical chart reminders, provider education, and point-of-care antibody testing significantly improved at least three study outcomes compared with a comparator or control. Interventions that simplified HCV testing, including dried blood spot testing, point-of-care antibody testing, reflex RNA testing, and opt-out screening, significantly improved testing outcomes compared with a comparator or control. Enhanced patient and provider support through patient education, provider care coordination, and provider education also significantly improved testing outcomes compared with a comparator or control. Integrated care and patient navigation or care coordination significantly improved linkage to care and the uptake of direct-acting antiviral treatment compared with a comparator or control. Interpretation: Several interventions to improve HCV care that address several key barriers to HCV care were identified. New models of HCV care must be designed and implemented to address the barriers faced by the population of interest. Further high-quality research, including rigorously designed randomised studies, is still needed in key populations. Funding: None.